Kosovo Country Economic Memorandum, November 2021 : Gearing Up for a More Productive Future - World Bank (World Bank, Washington, DC, 2022)
Kosovo, one of the youngest countries in an aging Europe, took its first steps on the road to greater prosperity a quarter of a century ago. Kosovo’s economy has experienced significant growth in recent years. The Coronavirus disease 2019 (COVID-19) pandemic has triggered Kosovo’s first ever recession in 2020. While spending on education has more than doubled, the quality of human capital needs to improve. And barriers to women’s economic empowerment need to be lifted. Proximity to major markets in Europe and a youthful population provide an opportunity for growth. Kosovo is one of the youngest countries in an aging Europe. Trade facilitation and logistics connectivity are getting better. Proximity to a large and affluent market, low taxes and labor costs, a resilient and liquid financial sector, and strong ties with its diaspora will help support growth.